Prospective evaluation of pain, swelling, and disability from copperhead envenomation. (15th March 2016) - Roth, Brett; Sharma, Kapil; Onisko, Nancy; Chen, Tiffany
Abstract: Context : In light of the existing controversy regarding antivenin treatment for copperhead envenomation, a more detailed analysis of the disability from this species is needed.Objective : Our objective was to prospectively determine the duration of pain, swelling, and functional disability, i.e., residual venom effects, in patients with copperhead envenomation.Methods : Patients with venomous snakebite reported to the North Texas Poison Center between April 2009 and November 2011 were assessed. Patients with confirmed envenomations were contacted by a specialist in poison information. Day zero was the day of the bite and verbal phone consent for study enrollment was obtained at that time. The patient (or their guardian) was contacted by phone daily thereafter, and asked to rate their pain, edema/swelling, and disability using the modified DASH and LEFS scales. Patients were followed to resolution of all symptoms or return to baseline.Results : About 104 cases of venomous snakebite were followed; of which 17 were excluded due to being a dry bites (5) or for having insufficient data during follow-up (11) or due to coagulopathy (1). Overall, residual venom effects from copperhead bites for most patients last between 7 and 13 days. Median time to complete pain resolution was 7 days (mean = 10.7 days). Median length of time to resolution of swelling was 10 days (mean = 13 days) and median length of time to resolution of functional disability was 9 days (mean = 12.2 days).Discussion : Residual venom effects from copperhead envenomation in this study had a slightly shorter duration than some other studies. Data are skewed due to outliers where residual venom effects lasted for up to 89 days. Initial reoccurrence of some symptoms may be seen. Antivenom (AV) is currently being used for a large percentage of patients with copperhead envenomation. Finally, no differences in duration of venom effects were seen based on age or location of bite.Conclusion : Our study suggests that residual venom effects from copperhead species persist for between 10 and 13 days but may persist for months. Future studies are necessary to identify risk factors for severe/prolonged injury and to define the benefit of AV in patients with copperhead envenomation.